2005
DOI: 10.1152/japplphysiol.00869.2004
|View full text |Cite
|
Sign up to set email alerts
|

Airway resistance due to alveolar gas compression measured by barometric plethysmography in mice

Abstract: . Airway resistance due to alveolar gas compression measured by barometric plethysmography in mice. J Appl Physiol 98: 2204 -2218, 2005. First published January 27, 2005 doi:10.1152/japplphysiol.00869.2004.-We developed a method for measuring airway resistance (R aw) in mice that does not require a measurement of airway flow. An analysis of R aw induced by alveolar gas compression showed the following relationship for an animal breathing spontaneously in a closed box: R aw ϭ A btVb/[Vt (Ve ϩ 0.5Vt)]. Here Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 26 publications
5
22
3
Order By: Relevance
“…Kumar et al [24], on the other hand, have demonstrated that IL‐13 −/− mice chronically exposed to OVA demonstrate significant reduction in inflammatory cells, sub‐epithelial fibrosis and mucus cell hyperplasia, but still developed AHR. These results with AHR are different from ours, possibly because of the use of the enhanced pause measurement in a body plethysmograph for assessing AHR by Kumar et al [25], a method that may not necessarily reflect changes in lung mechanics. Our results show that knocking out the Th2 cytokine gene cluster prevented allergen‐induced AHR to a similar extent as knocking out only IL‐13, placing IL‐13 as being most crucial for the expression of AHR.…”
Section: Discussioncontrasting
confidence: 99%
“…Kumar et al [24], on the other hand, have demonstrated that IL‐13 −/− mice chronically exposed to OVA demonstrate significant reduction in inflammatory cells, sub‐epithelial fibrosis and mucus cell hyperplasia, but still developed AHR. These results with AHR are different from ours, possibly because of the use of the enhanced pause measurement in a body plethysmograph for assessing AHR by Kumar et al [25], a method that may not necessarily reflect changes in lung mechanics. Our results show that knocking out the Th2 cytokine gene cluster prevented allergen‐induced AHR to a similar extent as knocking out only IL‐13, placing IL‐13 as being most crucial for the expression of AHR.…”
Section: Discussioncontrasting
confidence: 99%
“…This could be avoided in future experiments by conducting the entire study without opening the chamber, i.e., aerosolizing agonists to the mice within the chamber using special delivery systems (3,19). Incorporation of heating elements or warmed water (39,40,42) or decreasing the size or thickness of the chamber walls may also serve to stabilize the thermal conditions of the box interior. Alternatively, flow-type plethysmography has been described (49), which would minimize the effects of baseline thermal drift, although pose additional challenges, e.g., maintaining calibration.…”
Section: Discussionmentioning
confidence: 99%
“…One major concern with the use of an unheated plethysmograph was the potential for errors to arise in the computation of sRaw, from heating and humidification of inspired gas, which has been shown to cause the box pressure amplitude to nearly double (39,40,57). We explored this issue by performing a pilot experiment with conscious mice (BALB/c female, n ϭ 5, 21.6 -27.1 g), whereby sRaw was determined in the heated and humidified (37°C, 90% humidity) vs. unheated (26°C, 66% humidity) box.…”
Section: Methodsmentioning
confidence: 99%
“…Whole-body plethysmography remains the best choice to measureV E and frequency of apnoeas in unrestrained and minimally disturbed animals, which was desired in the present study. It has been suggested that determination of V T with this approach cannot discriminate the signal generated by heating and humidification of inspired air (Drorbough & Fenn, 1955;Mortola & Frappell, 1998) and the signal generated by compression of air during inspiration, when airway resistances are elevated (Lai-Fook & Lai, 2005). However, our values for V T of newborn mice [0.5-1 ml (100 g) −1 ] are in the same range as the values obtained with head-out plethysmography recordings (Mortola, 1984;Robinson et al 2000;Bissonnette & Knopp, 2001), a method that directly measures the pressure changes due to inspiration, and they are also consistent with values obtained by acoustic plethysmography in newborn mice (Daubenspeck et al 2008).…”
Section: Methodsmentioning
confidence: 99%